Eksplorasi Etnomatematika Alat Tradisional Dayak Kanayatn (Pasira’ Dan Salapa) Kalimantan Barat - Irena Christantya; Reni Astuti; Sandie Sandie (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
This research aims to identify and describe the ethnomathematics of the traditional tools of the Dayak Kanayatn Pasira' and Salapa tribes in Menjalin District, Landak Regency, West Kalimantan. The research method used is ethnomathematics with the research object being the traditional game of marbles. The data sources in this research consist of: research objects, namely Pasira' and Salapa, and related documents discussing Pasira' and Salapa. Data collection techniques are carried out through: observation and documentation. Based on the research results obtained and data analysis, it is concluded that in the traditional Pasira' and Salapa tools there are mathematical concepts, namely: the concept of building space in the Pasira' and Salapa shapes, namely cubes and blocks.